Designing a Math Picture Book to Stimulate Primary School Students’ Understanding of Properties of 2-D Shapes - Nurzayyana, Ayu; Putra, Zetra Hainul; Hermita, Neni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This study aims to determine the feasibility of a math picture book (MPB) on the properties of 2-D shapes designed for primary students, and to find out how it can stimulate primary students' understanding about the properties of 2-D shapes. The method used in this research is design research based on Plomp’s development model. The development research was carried out from designing MPB, validating with two experts, and testing with primary students in two stages, namely one-to-one and small group experiments. Based on experts’ reviews, the designed MPB met very valid criteria, and the students and teachers also provided positive responses to the quality of designed MPBs. From experimenting it to six primary students in the experiment, it shows that students could explain the properties of 2-D shapes after reading the MPB. Therefore, the developed MPB had a positive impact on students’ understand the properties of 2-D shapes.